التضخم واثره على الأداء المالي في مؤسسات التعليم العالي بالسودان بالتطبيق على كلية الشرق الأهلية: جامعة كسلا - د. مزمل عوض الكريم أحمد عثمان; د. محمد عمر المبارك عبد الكريم; د. سوزان عبد الله الفضل مختار (White Nile Journal for Studies and Research, 2022)
The study focuses its research on the universities and colleges in Kassala city. The study's problem is represented in a question; Does the inflation have a direct impact on the financial performance of the universities and colleges?, and to what extend does the financial performance' s impact on inflation. The study aims at declaring the inflation's impact on high education institutes' continuity, and to present how important the financial declaration as a source of decisions. The research hypotheses shows that the inflation has a negative reaction on revenues of the Sudanese universities and colleges. Inflation has a great influence on expenditure of the Sudanese universities and faculties. Ignoring inflation leads to discontinuation of Sudanese universities and faculties. The information of the study is collected from the previous studies related to the topic. In the practical framework, the study has used the exploration and dedication the methods, beside paraphrasing the problem and choosing hypotheses most important results are; Inflation lead to weakening the other investments revenues because of the long plans bids of the Sudanese universities, Inflation effect on the reservation of the Sudanese community's colleges, Inflation lead to inaccurate predictions and planning in the incomes of the Sudanese universities, Inflation causes the human cadres to emigrate from the Sudanese universities, Inflation causes many students to stop learning because of the bad economic circumstances, Inflation causes quality of learning become lower because of the human migration of the Sudanese universities. Inflation affect in financial decisions of the Sudanese universities, Inflation causes salaries to be high at the Sudanese universities, Inflation affect in distributing benefits which won't encourage investments in the Sudanese universities and Inflation raises learning fees costs of the, to make annual budgets along with inflation. phenomena to put on account to avoid closing universities. To make plans. and strategic studies about inflation impact in high studies institutes continuity. Explaining the importance of the financial performance and its role as a source of decisions at the Sudanese universities.